2008
DOI: 10.4103/0253-7613.40485
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and hypolipidemic activity of ethanolic extract of Salvadora oleoides in normal and alloxan-induced diabetic rats

Abstract: Objective:To find out the hypoglycemic and hypolipidemic activity of an ethanolic extract of the aerial part of Salvadora oleoides Decne in euglycemic and alloxan-induced diabetic albino rats.Materials and Methods:Diabetes was induced in albino rats by administration of alloxan monohydrate (120 mg/kg, i.p.). Normal as well as diabetic albino rats were divided into groups (n = 6) receiving different treatments: vehicle (control), ethanolic extract (1 g and 2 g/kg b.w), and standard antidiabetic drug tolbutamide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(58 citation statements)
references
References 20 publications
(15 reference statements)
6
52
0
Order By: Relevance
“…Production of this chemical is thought to be a synapomorphic character of the entire crown group of Brassicales [4]. Since time immemorial plants of genus Salvadora had been used in traditional Ayurvedic medicine for a wide variety of purported health benefits; including hypoglycemic and hypolipidemic [5], antimicrobial [6] and as an antibacterial toothbrush. A recent analysis of the feces of a critically endangered Lemur species endemic to Madagascar, golden-crowned Sifaka (Propithecus tattersale), revealed that a major portion of its diet was encompassed of the leaves of Salvadora angustifolia [7], exposing a small facet of its hidden ecological importance.…”
Section: Introductionmentioning
confidence: 99%
“…Production of this chemical is thought to be a synapomorphic character of the entire crown group of Brassicales [4]. Since time immemorial plants of genus Salvadora had been used in traditional Ayurvedic medicine for a wide variety of purported health benefits; including hypoglycemic and hypolipidemic [5], antimicrobial [6] and as an antibacterial toothbrush. A recent analysis of the feces of a critically endangered Lemur species endemic to Madagascar, golden-crowned Sifaka (Propithecus tattersale), revealed that a major portion of its diet was encompassed of the leaves of Salvadora angustifolia [7], exposing a small facet of its hidden ecological importance.…”
Section: Introductionmentioning
confidence: 99%
“…Another reported by Rubin et al [37] direct evidence for a protective effect of HDL in atherosclerosis has come from transgenic mice in which high levels of expression of apoprotein A-1 (apoA-1) increased the concentration of HDL and protected mice against diet induced atherosclerosis. These ameliorating effects clearly denote the anti-hyperlipidaemic potential of Syzygium cumini [38][39][40]. It could also be suggested that this antihyperlipidaemic effects of Syzygium cumini pass through a decrease in intestinal cholesterol absorption or a decrease in the biosynthesis of cholesterol specifically by decreasing the activity of HMG-CoA reductase inhibitors.…”
Section: Discussionmentioning
confidence: 76%
“…27 These results were also similar to the ethanolic extract of the aerial part of Salvadora oleoides Decne which produced a significant reduction (p<0.001) in blood glucose and also had beneficial effects ( P<0.001) on the lipid profile in euglycemic as well as alloxan-induced diabetic rats, although the reduction in the blood glucose and improvement in lipid profile was less than that achieved with the standard drug tolbutamide. 28 The fresh leaf aqueous extract of Clerodendrum capitatum (CC) at the doses of 100, 400 and 800 mg/kg/day administering for 14 days significant (p<0.05, p<0.001) showed the dose dependent hypoglycemic and hypolipidemic effects in the treated rats. 29 And flower extract from Sphagneticola trilobata (L.) Pruski at the dose 250 mg/kg administering for 4 weeks significant (p<0.05) reduced the blood glucose levels, total cholesterol and low density lipoprotein in the diabetics but this is not in the normal rats.…”
Section: -13mentioning
confidence: 99%